2020
DOI: 10.7717/peerj.10409
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural patterns of free roaming wild boar in a spatiotemporal context

Abstract: Although the almost worldwide distributed wild boar Sus scrofa is a well-studied species, little is known about the behaviour of autochthonous, free living wild boar in a spatiotemporal context which can help to better understand wild boar in conflict terms with humans and to find solutions. The use of camera traps is a favourable and non-invasive method to study them. To observe natural behaviour, 60 camera traps were placed for three months in a state forest of 17.8 km2 in the region of the Luneburg Heath in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…The apparent seasonal aspect of this effect could indicate that human disturbances in the different management zones differ seasonally (e.g., increased human activity in the agricultural fields in the transition zone) and that wild boars adaptively respond to such differences. In our study area, as well as in other study areas across Germany (Erdtmann & Keuling, 2020; Johann, Handschuh, Linderoth, Dormann, et al, 2020; Keuling et al, 2008b), wild boar spent more than half of the day resting (Figure 5). In our study, the active time that included movement, foraging, and social interactions was positively correlated with the night length (Figure 5b (compare also Keuling et al, 2008b)), indicating that wild boar diel activity is constrained to times when it is dark (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 65%
“…The apparent seasonal aspect of this effect could indicate that human disturbances in the different management zones differ seasonally (e.g., increased human activity in the agricultural fields in the transition zone) and that wild boars adaptively respond to such differences. In our study area, as well as in other study areas across Germany (Erdtmann & Keuling, 2020; Johann, Handschuh, Linderoth, Dormann, et al, 2020; Keuling et al, 2008b), wild boar spent more than half of the day resting (Figure 5). In our study, the active time that included movement, foraging, and social interactions was positively correlated with the night length (Figure 5b (compare also Keuling et al, 2008b)), indicating that wild boar diel activity is constrained to times when it is dark (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 65%
“…As was discussed above, trapping represents a highly stressful situation for the entrapped wild boars that exhibited signs of distress. The rescuer female had an erected mane or arched back 53 , both being displays of intimidating or threatening behaviours 54 and acute stress response (i.e., "flight or fight") 55 . The fact that she exhibited signs of piloerection in more than half of the photos in which she was present (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In detailed case studies conducted in semi-natural landscapes, 32-104 wild plant species were found to be foraged by wild boars [64,69], the closest to our study area [70] but identification of foraged plant species is limited by the methodologies applied (stomach and faeces analysis) [65]. Observation-based studies on behaviour and foraging (including grazing and rooting) of wild boar are scarce [71][72][73]. Observational studies on free-ranging domestic pigs are also rare and done on non-traditionally kept pigs grazing in enclosures [23,25].…”
Section: Introductionmentioning
confidence: 99%